Sistem Manajemen Keamanan Informasi (SMKI) di PT. Surveyor Indonesia Cabang Surabaya: Penerapan Standar ISO 27001:2013 - Prawiranata, R. Teddy Adiyanto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This article discusses the implementation of the Information Security Management System (ISMS) and the adoption of the ISO 27001:2013 standard at PT Surveyor Indonesia Surabaya Branch. The purpose of writing this article is to analyze the process of designing, implementing, and maintaining the IMS, as well as the integration of the ISO 27001:2013 standard in the company's business practices. The results of the article show that the implementation of the SMKI and the adoption of the ISO 27001:2013 standard have had a positive impact on improving the information security and overall performance of PT Surveyor Indonesia Surabaya Branch. However, there were some challenges and barriers faced during the implementation process, such as limited resources and resistance from employees. Nonetheless, the integration of ISO 27001:2013 standard in PT Surveyor Indonesia Surabaya Branch is not only formal compliance but also implemented in daily business practices to protect the company's critical information and ensure optimal information security. The writing of this article is expected to make a significant contribution to PT Surveyor Indonesia, the academic community, and information security practitioners, as well as being a valuable contribution in the context of implementing the ISO 27001:2013 standard in an increasingly connected business era.